Metallic nanoparticles grown in the core of femtosecond laser micromachined waveguides - Almeida, J. M. P.; Ferreira, P. H. D.; Manzani, D. [UNESP]; Napoli, M. [UNESP]; Ribeiro, Sidney José Lima [UNESP]; Mendonca, C. R. (American Institute of Physics (AIP), 2014)
3D-waveguides containing silver nanoparticles have been fabricated in tungsten lead-pyrophosphate glass by femtosecond laser micromachining. Nucleation and growth of nanoparticles occur in a single step process when high repetition rate laser (MHz) is employed, while an additional annealing is required for the irradiation using kHz laser system. The presence of nanoparticles locally changes the refractive index, and, therefore, the elliptical structures produced by direct laser writing were able to guide light. By increasing the pulse energy applied during the micromachining, the waveguide size increased from 2 to 30 mu m, while their propagation loss decrease from 1.4 to 0.5 dB/mm at 632.8 nm. (C) 2014 AIP Publishing LLC.